2021
DOI: 10.1108/rjta-11-2020-0121
|View full text |Cite
|
Sign up to set email alerts
|

Modest wear e-commerce: examining online purchase intent in Indonesia

Abstract: Purpose The study has three primary purposes, i.e. (1) to examine the determinants influencing customers’ online purchase intent for modest wear; (2) to measure the effects of electronic innovativeness, fashion innovativeness, perceived value, and trust on the intent to buy modest wear via the Internet; (3) to inspect how the factor “trust” can affect the “perceived value” of modest wear purchase through e-commerce; and (4) to explore the roles of “attitude” and “religiosity” in influencing customers’ intent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 54 publications
1
10
0
1
Order By: Relevance
“…Through online sales, sellers and buyers get many benefits. Sellers only need a little money for promotion, etc (Sumarliah et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Through online sales, sellers and buyers get many benefits. Sellers only need a little money for promotion, etc (Sumarliah et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Spears and Singh (2004) employed purchase intention as the consequences of attitude towards brands. Additionally, purchase intention of apparels in Indonesia has been examined and it is found that purchase intention is affected by trust and perceived value (Sumarliah, Khan, and Khan 2021). Bagozzi, Batra, and Ahuvia (2016) proved that brand love potentially be crucial to enhance the relation between customers and brands.…”
Section: Brand Loyalty and Positive Wommentioning
confidence: 99%
“…Moreover, few researchers have conducted studies in the halal fashion industry, examining the link between halal fashion SC and KM. To the best of the authors' knowledge, only five notable works by Sumarliah and her collaborators are relevant to this halal fashion SC-KM link (Sumarliah, 2021;Sumarliah, Khan, & Khan, 2021;Sumarliah, Li, & Wang, 2020;Sumarliah, Li, Wang, Moosa, & Sackey, 2021). Through their combined efforts, these researchers investigated these issues:…”
Section: Literature Review and Hypotheses Knowledge Management And Supply Chain In Halal Food Industrymentioning
confidence: 99%